Pengembangan Kompetensi Pegawai Negeri Sipil Pada Badan Kepegawaian dan Pengembangan Sumber Daya Manusia Kota Dumai - Neneng Lestari; Seno Andri; Adianto Adianto (Universitas Muhammadiyah Mataram, 2021)
Based on staffing data at the Dumai City Human Resources Development and Staffing Agency, it is known that employee competence is still an issue that needs attention, especially in terms of knowledge/intellectual competence (formal education), skills competency (structural training, technical/functional training, courses, stewardship), and experience competencies (tenure, position/leadership experience), and attitude competencies. The purpose of this research is to find out the development of civil servant competency in the Dumai City Human Resources Development and human resources development agency and analyze the factors that hinder the development of civil servant competency in the Dumai City Human Resources Development and Staffing Agency. This research uses qualitative methods that are descriptive. The result of this study is the development of civil servant competencies in the Agency for Personnel and Human Resources Development dumai competency development cycle is still not optimal and there are still factors that hinder the development of Civil Servant Competency in the Agency for Personnel and Human Resources Development.